2019
DOI: 10.1021/acsaem.9b01863
|View full text |Cite
|
Sign up to set email alerts
|

Microtuning of the Wide-Bandgap Perovskite Lattice Plane for Efficient and Robust High-Voltage Planar Solar Cells Exceeding 1.5 V

Abstract: Iodide-free tribromide-based perovskites, with their wide bandgap of over 2.0 eV, are highly regarded as potential candidates for a photoelectrochemical water splitting system and the topmost cell in tandem solar cell. Herein, we report on the importance of microtuning of the crystal lattice by cesium incorporation into the A-site on low temperature processed formamidinium lead tribromide (CH(NH 2 ) 2 PbBr 3 = FAPbBr 3 ) perovskite films. The partial incorporation of cesium bromide (CsBr) into the FAPbBr 3 fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…b) External quantum efficiency (EQE) spectra of variable‐composition perovskite and Si solar cells reported in refs. [ 37,142,195–202 ] . c,d) Schematic illustrations of a monolithic 2‐T tandem (c) and a mechanically stacked 4‐T tandem (d).…”
Section: Emerging Hybrid Tandem Solar Cellsmentioning
confidence: 99%
“…b) External quantum efficiency (EQE) spectra of variable‐composition perovskite and Si solar cells reported in refs. [ 37,142,195–202 ] . c,d) Schematic illustrations of a monolithic 2‐T tandem (c) and a mechanically stacked 4‐T tandem (d).…”
Section: Emerging Hybrid Tandem Solar Cellsmentioning
confidence: 99%
“…The partial incorporation of cesium bromide (CsBr) into the FAPbBr 3 film tunes crystal−lattice interactions, resulting in a high-purity cubic crystal system with preferred orientation. 24 Zhang et al introduced a molecule of urea and eventually a PCE of 10.61% and V OC of 1.56 V achieved with planar structured solar cells. 25 The research studies of iodide-based perovskite solar cells have shown that the defect of grain boundary in perovskite films is detrimental to charge transport and will induce energy loss.…”
Section: Introductionmentioning
confidence: 99%
“…Using sputtered ZnO as an electron transport layer can deposit quality inorganic material on top of the perovskite absorber, thereby obtaining stable p–i–n FAPbBr 3 devices with improved efficiency . Second, the grow process of the perovskite grain film has currently been regulated. A high-quality perovskite film is propitious to the charge transport and reducing the recombination. The partial incorporation of cesium bromide (CsBr) into the FAPbBr 3 film tunes crystal–lattice interactions, resulting in a high-purity cubic crystal system with preferred orientation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, other studies have focused on understanding the correlations between ion migration and these intrinsic properties. [11][12][13][14] In contrast, another set of studies found that TiO 2 , the most commonly used electron-selective layer (ESL), contributes to the occurrence of J-V hysteresis in PSCs, possibly because of its low electron mobility, chemical reactivity with the perovskite layer, and interfacial defect states. [15][16][17][18] Interesting points are the dependence of hysteresis on the contact materials and the influence of interfacial materials on ion migration.…”
Section: Introductionmentioning
confidence: 99%